Proof of Chudnovsky Series for 1/π(PI)

2 comments
In 1988 D. V. Chudnovsky and G. V. Chudnovsky (now famous as "Chudnovsky Brothers") established a general series for π by extending Ramanujan's ideas (presented in this series of posts). It can be however shown that their general series can be derived using Ramanujan's technique. Chudnovsky's approach has the advantage that using class field theory the algebraic nature of parameters in the general series can be determined and this greatly aids in the empirical evaluation of the parameters and thereby providing an actual series consisting of numbers.

In this post we shall not focus on the algebraic nature of parameters in the Chudnovsky's general series as it involves the deep and complicated class field theory. Rather we will show that the Chudnovsky series can be obtained via Ramanujan's technique and thereby furnish a proof of the Chudnovsky general series.

The Chudnovsky Series for 1/π

We use the notation from the last two posts for Ramanujan's Lambert series: P(q)=124(q1q+2q21q2+3q31q3+)Q(q)=1+240(q1q+23q21q2+33q31q3+)R(q)=1504(q1q+25q21q2+35q31q3+)
Let n>3 be an integer and we write Pn=P(eπn),Qn=Q(eπn),Rn=R(eπn)jn=1728Q3nQ3nR2nbn=n(1728jn)an=bn6{1QnRn(Pn6πn)}
then Chudnovsky brothers establish the following general series for 1/π: 1π=1jnm=0(6m)!(3m)!(m!)3an+mbnjmn
We will show that this series is the same as series (21) in this post namely 1π=m=0(1/6)m(5/6)m(1/2)m(m!)3(A+mB)Jmn
where Jn=27G48n(G24n4)3A=2nG24n1(G24n4)3+G12nG24n4{n3(12k2)Rn(k,k)6}B=n1Jn
and this series is derived using Ramanujan's technique.

The verification that both the series (1) and (2) are same (but written in completely different notation) requires that we establish the following relations: (6m)!(3m)!=123m(1/6)m(5/6)m(1/2)m=1728m(1/6)m(5/6)m(1/2)m
Jn=1728jn=Q3nR2nQ3n
A=anjn
B=bnjn
The first identity regarding factorials is easy to establish once we observe that for each factor in denominator (3m)! we have twice that number as a factor in numerator and thus by cancellation we get (6m)!(3m)!=23m1357(6m1)=123m163656766m16=123m(1/6)m(5/6)m(1/2)m=1728m(1/6)m(5/6)m(1/2)m
In what follows we will put x=G24n whenever suitable to simplify the calculations (as well as typing). Using identities (21),(22) from the last post we can see that Q3nR2nQ3n=(14G24n)3(12k2)2(1+8G24n)2(14G24n)3=(14G24n)3(1G24n)(1+8G24n)2(14G24n)3=(G24n4)3(G24n1)(G24n+8)2(G24n4)3=(x4)3(x1)(x+8)2(x4)3=x312x2+48x64(x1)(x2+16x+64)(x4)3=x312x2+48x64(x3+15x2+48x64)(x4)3=27x2(x4)3=27G48n(G24n4)3=Jn
so that relation (4) is established.

We next establish (6) as it is easier to handle compared to (5). We have then bnjn=n(1728jn)jn=n(11728jn)=n(1Jn)=B
To establish (5) we need to proceed in multiple steps. The idea is to express an,bn in terms of Gn. We start with the simpler bn and we have: bn=n(1728jn)=1728n(1jn1728)=1728n(11Jn)=1728n(1+(G24n4)327G48n)=1728n(1+(x4)327x2)=1728n((x4)3+27x227x2)=1728n((x1)(x+8)227x2)=8(x+8)xn(x1)=8(G24n+8)G24nn(G24n1)
Next we need to handle Pn. Let q=eπn and then Pn=P(q). By equation (9) of this post (note that the definition of P(q) given there is different from what is being used in this post and accordingly P(q) of that post matches with P(q2) of the current post) we have: P(q2)=(2Kπ)2Rn(k,k)2n+3πn=(2Kπ)2(Rn(k,k)2n+3π4K2n)
and from equation (14) of the previous post we have: P(q2)=(2Kπ)2(3EK+k22)
so that 3EK+k22=Rn(k,k)2n+3π4K2n6EK+2k24=Rn(k,k)n+3π2K2n6EK+4k25=Rn(k,k)n+3π2K2n+2k21
and using equation (23) of last post we get: Pn=P(q)=(2Kπ)2(Rn(k,k)n+3π2K2n+2k21)=(2Kπ)2(Rn(k,k)n+2k21)+6πnPn6πn=(2Kπ)2(Rn(k,k)n+2k21)
From equations (21),(22) of last post we now have: QnRn(Pn6πn)=(14G24n)(Rn(k,k)n+2k21)(12k2)(1+8G24n)=x4(12k2)(x+8)Rn(k,k)nx4x+8
and therefore an=bn6{1QnRn(Pn6πn)}=4(x+8)3xn(x1)(2(x+2)x+8x4(12k2)(x+8)Rn(k,k)n)=83x(x+2)n(x1)43xx412k2Rn(k,k)x1=83x(x+2)n(x1)43x(x4)xx1Rn(k,k)x1=83x(x+2)n(x1)4(x4)3xRn(k,k)
Note that in the above derivation we have used the fact that 12k2=1G24n=x1x
and the same relation would be used in derivation which follows.

Finally we can see that anjn=an1728/Jn=anx8(x4)3=x8(x4)3(83x(x+2)n(x1)4(x4)3xRn(k,k))=x+23n(x1)(x4)3xx4Rn(k,k)6=x4+63n(x1)(x4)3xx4Rn(k,k)6=13n(x1)x4+2nx1(x4)3xx4Rn(k,k)6=n3xx4(12k2)+2nx1(x4)3xx4Rn(k,k)6=2nx1(x4)3+xx4(n3(12k2)Rn(k,k)6)=2nG24n1(G24n4)3+G12nG24n4(n3(12k2)Rn(k,k)6)=A
and thus the relation (5) is established. This completes the proof of Chudnovsky's series (1).

Print/PDF Version

2 comments :: Proof of Chudnovsky Series for 1/π(PI)

Post a Comment

  1. Superb Proofs ... but I did not understand what R_n(k,k') stood for?

  2. @Shivam Patel,
    To understand Rn(k,k) you need to also go through the linked post http://paramanands.blogspot.com/2012/03/modular-equations-and-approximations-to-pi-part-1.html

    This is one of most important and remarkable achievements of the Indian genius Ramanujan.